Linking Personal Values to Energy-Efficient Behaviors in the Home. (May 2013) - Mirosa, Miranda; Lawson, Rob; Gnoth, Daniel
Laddering techniques are used to identify personal values underlying a range of 21 potential energy-saving behaviors or purchases. At an individual level, ladders (or means-end chains) are quite simple; when aggregated, however, they are complex and show many different paths between underlying values and behaviors. The values identified can promote energy-efficient behaviors or act as obstacles to change. The value "pleasure, " for example, was found to influence energy-efficient behavior, such as hanging the laundry on the line, and inefficient behavior, such as taking long showers. Results show that values relating to "achievement" are most influential on the way people use energy in the home. Thus, social marketing campaigns promoting energy efficiency and conservation should tap into achievement values such as capability and intelligence because these campaigns are more likely to be effective than those that use other types of appeal.